Actual Hospital Costs Associated With Severe Maternal Morbidity Compared to Uncomplicated Pregnancies [01L]. (May 2020) - Debbink, Michelle; Metz, Torri; Silver, Robert R.; Varner, Michael; Smid, Marcela Carolina; Einerson, Brett
Abstract : INTRODUCTION: Severe maternal morbidity (SMM) is rising, but true costs are unknown. We aimed to assess actual hospital costs of pregnancies complicated by SMM compared to uncomplicated pregnancies. METHODS: We conducted a retrospective nested case-control study at a single US institution from 1/2014–6/2017. Cases had at least one of 25 ICD-9 or 10 codes defined as SMM by the CDC. We excluded cases with transfusion as a sole SMM indicator or that were incorrectly coded on chart review. Controls were selected randomly from all deliveries +/- 60 days from case delivery at a 5:1 ratio. Cost data included actual costs/utilization compiled via time- and activity-based accounting. Total costs were computed across pregnancy episodes. Adjusted multivariate regression was used to compare costs. Covariates were identified via backward stepwise regression. Relative costs are reported. IRB approval was obtained. RESULTS: 12, 578 women delivered during the study period. 454 (3.6%) had ICD-9/10 codes meeting SMM criteria, and 170 (1.4%) had correctly-coded non-transfusion SMM events after chart review. Among cases, cesarean delivery and preterm birth were more common. In adjusted models, SMM was associated with increased hospital costs (114.5%; 95% CI 98.9%–130.1%). Predicted absolute cost increases are over $10, 000/pregnancy episode. Stratified models show SMM at term is associated with a 122.7% (95% CI 108.6%–136.8%) cost increase, and preterm deliveries with a 67.9% (95% CI 33.2%–102.6%) increase. CONCLUSION: SMM is associated with higher hospital costs compared to uncomplicated pregnancies. Identifying preventable SMM and implementing effective reduction strategies may result in healthcare savings.